Pengaruh Strategi Numbered Heads Together (Nht) Dan Two Stay Two Stray (Ts-Ts) Terhadap Hasil Belajar Matematika Ditinjau Dari Aktivitas Belajar Siswa Kelas VII Di SMP Muhammadiyah 4 Surakarta Tahun Ajaran 2015/2016 - KHOTIMAH, KHUSNUL; , Drs. Slamet HW, M.Pd (2016)
The purpose of this study to understanding : (1) the effect of learning strategies Numbered Heads Together and Two Stay Two Stray on learning outcomes in mathematic, (2) the influence of students' learning activity learning outcome in mathematic, and (3)the interaction between learning strategy and student's learning activity to learning outcome in mathematic. The type of the research is experiment with quasi experimental design. The population of the research was all student of VII Grade of SMP Muhammadiyah 4 Surakarta of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methode of data collection use test, kuasioner, and documentation. Data analyzed by analysis of variance with two obtained: (1) Fa=4,901> Ftable =4,03. So, the effect of strategy numbered heads together and two stay two stray to learning outcome in mathematic, (2) Fb=12,891> Ftable=3,18.So, there is effect of student's learning activity for learning outcome in mathematic, and (3) Fab = 2,278 < Ftable= 3,18. So, there is no interation between discovery learning strategy and students' learning activity to learning outcome in mathematic.